1982
DOI: 10.1139/z82-061
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the White-throated Sparrow: habitat occupancy and nest-site selection

Abstract: We analysed several vegetational variables in four populations of White-throated Sparrows (Zonotrichia albicollis) to determine if differences exist between the white-stripe (WS) and tan-stripe (TS) morphs at the level of the macrohabitat (territory) and the microhabitat (nest site). Univariate and discriminant function analyses revealed that trees were farther apart, more light penetrated to the forest floor, and fewer shade-tolerant plants occurred in territories of WS than TS males. There was little differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Previous work on this species suggests that male morphs might partition habitats (Rising and Shields 1980) and establish territories in areas that differ in ''openness'' (Knapton and Falls 1982). Preliminary study of our population in the Adirondack Park of New York, USA, suggests that such segregation does not exist (Tuttle 1993).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous work on this species suggests that male morphs might partition habitats (Rising and Shields 1980) and establish territories in areas that differ in ''openness'' (Knapton and Falls 1982). Preliminary study of our population in the Adirondack Park of New York, USA, suggests that such segregation does not exist (Tuttle 1993).…”
Section: Introductionmentioning
confidence: 68%
“…A previous study reported differences in the proportion of open habitat in white and tan male territories, using standard aerial photography to delineate open areas (Knapton and Falls 1982). We attempted to compare our results by collapsing our vegetation classes into ''open'' and ''closed'' habitat types.…”
Section: Vegetation Structurementioning
confidence: 99%
“…However, the ratio of WS:TS was still high in ground traps (36 WS:20 TS). Alternatively, TS individuals might choose to refuel in poorer quality habitat, as they do on breeding grounds (Knapton and Falls ), or further inland from the Lake Erie shore to avoid competition with WS individuals as seen in other species (Yong et al , Cerasale and Guglielmo ).…”
Section: Discussionmentioning
confidence: 99%
“…During this study (see also Knapton and Falls 1982), we identified the male and female in each of 180 pairs. Of these, 1 17 pairs (65%) were WS male X TS female and 60 pairs (33%) were TS male x WS female.…”
Section: Negative Assortative Matingmentioning
confidence: 99%
“…In this paper, We report On relative contributions coloured (tan-striped TS) rnorph of the White-throated to nestlings of male and female parents among different Sparrow (Zonotrichia albicollis) (Lowther 196 1 ; pair types in the White-throated Spanow ~o w t h e r and Falls 1968; Rising and Shields 1980; Knapton and Falls 1982). This polymorphism appears to be maintained by negative assortative mating; WS birds of either sex.usually pair with TS birds of the opposite sex (Lowther 196 1 ;Thorneycroft 1976; see below).…”
Section: Introductionmentioning
confidence: 99%